Evaluation and engineering applications of the in situ stress state of deep tight sandstone reservoirs in the Xujiahe Formation of the Yingshan-Longgang in the central Sichuan Basin - Gao, Songyang; Deng, Hucheng; Yan, Weilin; Yin, Shujun; Zhou, Jiayu; Wen, Zheng; Guo, Yunfei; Zhang, Bo; Li, Chuang; Yang, Xiaolei; Xia, Wenhao; Huang, Tao (Frontiers in Earth Science, 2023)
According to geological surveys, the Xujiahe Formation in the Yingshan-Longgang area has abundant tight oil and gas resources. However, the complex geological conditions and insufficient data on the magnitude and direction of in-situ stress in this area have restricted the exploration and development of these resources. In this study, the evaluation of the magnitude and direction of the in-situ stress was carried out based on the analysis of experimental tests such as acoustic emission, wave velocity anisotropy, and paleomagnetism, which provides a basis for the selection of the fracture modification layer and the deployment orientation of horizontal wells in the study area. The obtained results show that the three-way stress in the Xujiahe Formation is in a slip stress state, and it gradually increases with increasing depth. Moreover, it is found that the three-way stress in the Longgang area is relatively larger under the influence of the burial depth; The average azimuth of the maximum horizontal principal stress in the Xujiahe Formation is N100°E, and the maximum horizontal principal stress is affected by tectonic deformation. Furthermore, the performed analyses reveal that the azimuth of the maximum horizontal principal stress in the Yingshan area is deflected counterclockwise. Considering the influence of the minimum horizontal principal stress and the longitudinal change of the two-way stress difference on the hydraulic fracture expansion pattern, the middle and upper sections of the XuⅡ be selected for fracture reconstruction. Similarly, considering the azimuth of the maximum horizontal principal stress and the distribution of natural fractures, the azimuth of the horizontal well deployment is N20°-30°E.